Material and energy loss due to human and machine error in commercial FDM printers. (1st April 2017) - Song, Ruoyu; Telenko, Cassandra
Abstract: Additive manufacturing is thought to have environmental benefits. However, material waste and energy consumption could be larger than expected due to human or printer error. In general, fused deposition modeling (FDM) printers using ABS plastic have three stages for parts fabrication: the standby period, preheating process and the printing process. In practice, the quantity of support material is influenced by the part orientation and settings of the printing. Material waste and energy consumption for commercial FDM printers using ABS material in a heavily utilized open shop were analyzed. The failed prints were classified into 9 different categories and analyzed. The data indicated that about 34% of the plastic used in the open studio was wasted. Only considering the failed prints as the extra amount of material consumed under realistic conditions, the mass of material lost to failed builds was about 2.22 times what might be estimated in a controlled process study. For energy consumption, the standby period and preheating time vary for every job, which results in variability of energy consumption. The printing time is based on the geometry of parts being built, the part printing orientation and setting of that print. From collected data, the preheating energy consumption is 0.835 MJ/kg, the printing is 21.5 MJ/kg, and the standby is 9.5 MJ/kg. Moreover, suggestions to reduce the building cost for each failure type are given. A life cycle inventory (LCI) combining the material waste and energy consumption data of FDM reveals that actual energy consumption may be 50% more than under ideal conditions. Highlights: Failure rates of FDM resulted in 2.2 times the waste of a controlled process study. Calibration problems contribute to a large portion of the material waste. Reducing preheating and standby time can reduce the energy consumption of FDM. Energy LCI of FDM in use was about 50% greater than under ideal conditions.